2021
DOI: 10.21203/rs.3.rs-591145/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of MMP9 Polymorphism With Myocardial Infarction

Abstract: Myocardial Infarction (MI) is the most common type of coronary heart disease characterized by pain, nausea, sweating, shortness of breath and abnormal heartbeat. Current study was conducted to identify the susceptibility of the MMP-9 gene among families affected with myocardial infarction in the Pakistani population. A family clustering study based on 5 families having MI patients was conducted. Blood samples from MI patients and their family members were collected for further genetic analysis. Patients were w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Regarding the allelic frequencies, the statistical analysis showed that the T-allele is a risk allele that contributes to a significant association (p<0.05) of the rs3918242 polymorphism with myocardial infarction (higher allelic frequency in patients versus controls). What can be concluded from this study is that both mentioned polymorphisms of the MMP9 gene have a significant role in the development of myocardial infarction, whereas the TT and CT genotypes of rs3918242 indicate that the person is a carrier and may later develop myocardial infarction [30].…”
Section: Table 4 Presentation Of Genotypic and Allelic Frequencies Of...mentioning
confidence: 67%
“…Regarding the allelic frequencies, the statistical analysis showed that the T-allele is a risk allele that contributes to a significant association (p<0.05) of the rs3918242 polymorphism with myocardial infarction (higher allelic frequency in patients versus controls). What can be concluded from this study is that both mentioned polymorphisms of the MMP9 gene have a significant role in the development of myocardial infarction, whereas the TT and CT genotypes of rs3918242 indicate that the person is a carrier and may later develop myocardial infarction [30].…”
Section: Table 4 Presentation Of Genotypic and Allelic Frequencies Of...mentioning
confidence: 67%